Assessment of groundwater quality using Physico-chemical analyses of Sahel-Doukkala region - Benmhammed Ayoub (EDP Sciences, 2021)
Water quality preservation represents one of the biggest challenges the world is facing nowadays. In Morocco, water quality decline is among the significant problems facing the country’s water sector. Geographic Information System (GIS) is an effective and useful tool for interpreting, evaluating and displaying spatial data for water resources management. In order to assess the Physico-chemical characteristics of groundwater of the Sahel-Doukkala aquifers, water samples were collected from 50 points well distributed in the study area, analysed according to standard methods, and the results were interpreted using the geographic information system (GIS) technique. There was an important spatial variability in the studied parameters and element concentrations (T°, pH, EC, Cl-, Ca2+, Mg2+, Sr, B and Na+), revealing that the aquifers lithology, sea intrusion and the agriculture methods are the main factors influencing the water nature in the study area.